2011
DOI: 10.1074/jbc.m110.187872
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation Controls Dopamine Transporter Kinetics, Degradation, and Protein Kinase C-dependent Regulation

Abstract: Palmitoylation is a lipid modification that confers diverse functions to target proteins and is a contributing factor for many neuronal diseases. In this study, we demonstrate using [ 3 H]palmitic acid labeling and acyl-biotinyl exchange that native and expressed dopamine transporters (DATs) are palmitoylated, and using the palmitoyl acyltransferase inhibitor 2-bromopalmitate (2BP), we identify several associated functions. Treatment of rat striatal synaptosomes with 2BP using lower doses or shorter times caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
108
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(118 citation statements)
references
References 68 publications
7
108
2
1
Order By: Relevance
“…The Vaughan laboratory more recently provided evidence that the trafficking-independent effects of PKC may involve regulation of palmitoylation of DAT. Inhibition of DAT palmitoylation by the palmitoyl acyltransferase inhibitor 2-bromopalmitate in rat striatal synaptosomes led to decreases in the V max of DA uptake independent of changes in DAT surface levels, supporting a role for this modification in trafficking-independent regulation of DAT activity (Foster and Vaughan, 2011). Importantly, activation and inhibition of PKC by PMA/BIM-1 decreased and increased palmitoylation of DAT, respectively, and mutation of the PKC target Ser7 to alanine abolished these effects on palmitoylation (Moritz et al, 2015).…”
Section: Regulation Of Dopamine Transporter Membranementioning
confidence: 85%
See 1 more Smart Citation
“…The Vaughan laboratory more recently provided evidence that the trafficking-independent effects of PKC may involve regulation of palmitoylation of DAT. Inhibition of DAT palmitoylation by the palmitoyl acyltransferase inhibitor 2-bromopalmitate in rat striatal synaptosomes led to decreases in the V max of DA uptake independent of changes in DAT surface levels, supporting a role for this modification in trafficking-independent regulation of DAT activity (Foster and Vaughan, 2011). Importantly, activation and inhibition of PKC by PMA/BIM-1 decreased and increased palmitoylation of DAT, respectively, and mutation of the PKC target Ser7 to alanine abolished these effects on palmitoylation (Moritz et al, 2015).…”
Section: Regulation Of Dopamine Transporter Membranementioning
confidence: 85%
“…This is a critical issue as these regions support the binding of a growing class of interacting proteins that dictate transporter localization, stability, and activity. Cytoplasmic domains also contain sites of posttranslational modifications, including lipidation (Foster and Vaughan, 2011) and phosphorylation . Together, these modes of posttranslational regulation amply demonstrate that the MA reuptake process itself is under the control of signaling proteins whose actions provide additional points of control for MA signaling.…”
mentioning
confidence: 99%
“…These resi-dues are not necessary for PKC-stimulated endocytosis of the transporter (21,22), but their role in kinetic regulation of uptake has not yet been investigated. DAT is also palmitoylated on Cys-580 at the membrane-cytoplasm interface of the most C-terminal transmembrane helix (17). Acute inhibition of transporter palmitoylation enhances PKC-stimulated downregulation and induces significant trafficking-independent decreases in transport V max (17), also suggesting a role for this modification in catalytic regulation of transport.…”
Section: The Dopamine Transporter (Dat)mentioning
confidence: 96%
“…Most studies to date have focused on membrane trafficking as the mechanism underlying PKC-induced transport reductions (10 -14), but recent findings have shown that significant levels of downregulation are retained when transporter endocytosis is blocked or impaired (15)(16)(17), indicating the presence of a kinetic regulatory mechanism that operates in concert with internalization.…”
Section: The Dopamine Transporter (Dat)mentioning
confidence: 99%
“…Palmitoylation regulates DAT function and structure by maintaining V max and reducing PKC-mediated plasma membrane turnover (Foster and Vaughan, 2011). Although much of this process requires elucidation, palmitoylation is important in activity-driven changes in synapse morphology and function (Kang et al, 2008) and may serve as a future target for pharmacological manipulation.…”
mentioning
confidence: 99%